Structural and short-term causes in Spanish-American Independence in Historiography - Arpa Calachua, Florentino (2021)
It is important to know the explanations about the causes of Latin American peoples, development and complex connection in commemoration of their Bicentenary independence. Research identifies causes of internal and external order in most cases, without considering the current relationship between them. The research proposal about the independence causes has allowed to group them into structural and short-term causes. Structural causes allow us to recognize long term changes which humanity had already faced as the nineteenth century approached. Economically, the feudal system was competing with the capitalist system; politically, the overseas powers were confronting each other for the domination of the known world; in the social aspect, the social classes were facing serious contradictions; ideologically, the change from theocentric to anthropocentric thinking led to a questioning of the existing world. The second (short-term causes) are those ones which accelerate and brought to light the crisis that existed between 1805 and 1814. This crisis worsened with the defeat of the Spanish fleet in Trafalgar in 1805, which allowed the control and influence of England in the economy and politics of the Spanish-American colonies; another cause was the Napoleonic invasion of Spain in 1808, which originated a power vacuum, which was harnessed by the Spanish provinces in the New World. Considering the structural and short-term causes within the work of history will allow to carry out the connection between them with the local ones enabling the proper historical interpretation.